An assemblage of Frankia Cluster II strains from California contains the canonical nod genes and also the sulfotransferase gene nodH. (December 2016) - Nguyen, Thanh; Wibberg, Daniel; Battenberg, Kai; Blom, Jochen; Vanden Heuvel, Brian; Berry, Alison; Kalinowski, Jörn; Pawlowski, Katharina
Abstract Background The ability to establish root nodule symbioses is restricted to four different plant orders. Soil actinobacteria of the genusFrankia can establish a symbiotic relationship with a diverse group of plants within eight different families from three different orders, the Cucurbitales, Fagales and Rosales. Phylogenetically, Frankia strains can be divided into four clusters, three of which (I, II, III) contain symbiotic strains. Members of Cluster II nodulate the broadest range of host plants with species from four families from two different orders, growing on six continents. Two Cluster II genomes were sequenced thus far, both from Asia. Results In this paper we present the firstFrankia cluster II genome from North America (California), Dg2, which represents a metagenome of two major and one minor strains. A phylogenetic analysis of the core genomes of 16Frankia strains shows that Cluster II the ancestral group in the genus, also ancestral to the non-symbiotic Cluster IV. Dg2 contains the canonicalnod genesnodABC for the production of lipochitooligosaccharide Nod factors, but also two copies of the sulfotransferase genenodH. In rhizobial systems, sulfation of Nod factors affects their host specificity and their stability. Conclusions A comparison with thenod gene region of the previously sequenced Dg1 genome from a Cluster II strain from Pakistan shows that the common ancestor of both strains should have containednodABC andnodH. Phylogenetically, Dg2 NodH proteins are sister to rhizobial NodH proteins. AglnA -based phylogenetic analysis of all Cluster II strains sampled thus far supports the hypothesis that Cluster IIFrankia strains came to North America withDatisca glomerata f ollowing the Madrean-Tethyan pattern.